The unilateral and bilateral control of motor unit pairs in the first dorsal interosseous and paraspinal muscles in man. - Marsden, J; Farmer, S; Halliday, D; Rosenberg, JR; Brown, P (1999)
1. The discharges of two motor units were identified in an intrinsic hand muscle (first dorsal interosseous, FDI) or an axial muscle (lumbar paraspinals, PSP) in ten healthy subjects. Each motor unit was situated in the homologous muscle on either side of the body (bilateral condition) or in the same muscle (ipsilateral condition). The relationship between the times of discharge of the two units was determined using coherence analysis. 2. Motor unit pairs in the ipsilateral FDI showed significant coherence over the frequency bands 1-10 Hz and 12-40 Hz. Motor units in the ipsilateral PSP were significantly coherent below 5 Hz. In contrast there was no significant coherence at any frequency up to 100 Hz in the bilateral FDI condition and only a small but significant band of coherence below 2 Hz in the bilateral PSP condition. 3. Common drive to motor units at frequencies of < 4 Hz was assessed by cross-correlation of the instantaneous frequencies of the motor units. A significantly higher coefficient was found in the ipsilateral FDI, ipsi- and bilateral PSP compared with shifted, unrelated data sets. This was not the case for the bilateral FDI condition. 4. The presence of higher frequency coherence ( > 10 Hz) in the ipsilateral FDI condition and its absence in ipsilateral PSP is consistent with a more direct and influential cortical supply to the intrinsic hand muscles compared with the axial musculature. The presence of low frequency drives (< 4 Hz) in the bilateral PSP condition and its absence in the bilateral FDI condition is consistent with a bilateral drive to axial, but not distal, musculature by the motor pathways responsible for this oscillatory input.